Allergic bronchopulmonary disease caused by Curvularia lunata and Drechslera hawaiiensis. Issue 5 (May 1981) - McAleer, R; Kroenert, D B; Elder, J L; Froudist, J H
Abstract : Three patients who developed bronchoceles caused by fungi other than Aspergillus sp are described. The first patient presented for investigation of a lesion at the right hilum on chest radiograph and a raised blood eosinophil count. A bronchogram showed complete block of the apical segmental bronchus which at operation was shown to be caused by inspissated material. The second patient was investigated because of a cough productive of plugs of sputum and irregular opacities in both upper zones on chest radiograph and a raised blood eosinophil count. This only cleared after one month on high dose oral prednisone therapy. The third patient with a previous history of left lingular pneumonia and bronchiectasis of the lingular segment of the left upper lobe was investigated three years later for right basal shadowing and a raised blood eosinophil count. The radiograph cleared after one month on high dose oral prednisone treatment. The aetiological agents in these cases were dematiaceous hyphomycetes, fungi ubiquitous in nature, and also agents of plant disease. The causal fungi, Curvularia lunata and Drechslera hawaiiensis, have on a few occasions been reported as causing human disease but in cases quite dissimilar to the three reported here. Septate branching dematiaceous mycelium was consistently seen in the clinical material and isolated from successive sputum specimens from each patient. Immunodiffusion tests from the third patient gave positive results for both fungi. Intraperitoneal inoculations of C lunata and D. hawaiiensis into Swiss white mice proved the pathogenicity of these isolates.